Pengaruh Penyuluhan terhadap Perilaku Higiene Menstruasi pada Remaja Pondok Pesantren Yasrib dan SMA Negeri 1 Kabupaten Soppeng - Rezkiani Kas, Sri; Darlis, Idhar (Jurnal Keolahragaan JUARA, 2024)
Personal hygiene of the genital organs is an important part to prevent the occurrence of Reproductive Tract Infections (ISR). ISR occurs due to poor hygiene behavior and to prevent it by maintaining the cleanliness of the reproductive organs. Hygiene during menstruation is very necessary to avoid infectious diseases which can later be very detrimental and there is infection of the reproductive organs caused by bacteria, general symptoms of bacterial infection that are often encountered during menstruation such as: fever, inflammation of the vaginal surface, itching in the vagina. skin. This study aims to analyze the effect of counseling using audiovisual media on improving behavior (attitudes) about menstrual hygiene in adolescent girls at Yasrib Islamic Boarding School and State High School 1 Soppeng District. The type of research used is a quasi-experimental with The Nonrandomized Pre-test Post-test Control Group Design. Based on the results of the analysis showed that there was a significant difference in attitudes (0.000) before and after being given counseling in the intervention group. It is suggested that awareness needs to be increased to maintain personal hygiene and apply it as a preventive measure so as not to contract the disease